2020
DOI: 10.3390/cancers12030702
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Mutation Is Associated with STAT3 Activation in CD30+ ALK− ALCL

Abstract: Peripheral T-cell lymphomas (PTCL) are a heterogeneous, and often aggressive group of non-Hodgkin lymphomas. Recent advances in the molecular and genetic characterization of PTCLs have helped to delineate differences and similarities between the various subtypes, and the JAK/STAT pathway has been found to play an important oncogenic role. Here, we aimed to characterize the JAK/STAT pathway in PTCL subtypes and investigate whether the activation of the pathway correlates with the frequency of STAT gene mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Moreover, no significant differences were found between mutation status of these genes with age, gender, disease stage, eastern cooperative oncology group performance status or age-adjusted international prognostic index (AA-IPI). As expected [ 9 , 13 , 15 ], expression of p-STAT3 (Y705) was detected at a high level in all ALK− ALCL patients harboring STAT3 mutations, although low/medium expression of p-STAT3 was also detected in STAT3 wild-type patient tumors (Fig. S4 , Table S6 ).…”
Section: To the Editorsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, no significant differences were found between mutation status of these genes with age, gender, disease stage, eastern cooperative oncology group performance status or age-adjusted international prognostic index (AA-IPI). As expected [ 9 , 13 , 15 ], expression of p-STAT3 (Y705) was detected at a high level in all ALK− ALCL patients harboring STAT3 mutations, although low/medium expression of p-STAT3 was also detected in STAT3 wild-type patient tumors (Fig. S4 , Table S6 ).…”
Section: To the Editorsupporting
confidence: 83%
“…Despite the distinction between the two sALCL subtypes, frontline treatment for adults is similar and is based on CHOP or CHOEP, instead pediatric ALCL patients are mainly treated following the ALCL99 protocol [6][7][8]. Whilst high-throughput genomic studies in sALCL have shown recurrent genetic alterations, their association with outcome has not been fully investigated [9][10][11][12][13].…”
Section: To the Editormentioning
confidence: 99%
“…JAK/STAT mutations were also identified in patients with the rare and aggressive T-cell prolymphocytic leukemia (T-PLL), pointing towards a possible mode of transformation [25]. Additionally, STAT3 (and not STAT5B) mutations were identified in multiple peripheral T-cell lymphomas (PTCL), as well as high pY-STAT3 expression, particularly in angioimmunoblastic T-cell lymphoma (AITL) and anaplastic large cell lymphoma (ALCL) patient samples, two different PTCL cancer types [26]. From an inhibition perspective, a derivatized indole was shown to be effective in both chronic myeloid leukemia (CML) and acute myeloid leukemia (AML), as well as aggressive STAT5-N642H tumors [27].…”
Section: Chapter 1: Targeting Stat3/5 In Hematopoietic Cancersmentioning
confidence: 99%
“…Activating point mutations of STAT3 and/or JAK1 have been identified in 18% of nodal ALK- ALCLs and in 5% of C-ALCLs [ 50 ]. Another study of PTCL identified in ALK- ALCLs the highest rate of STAT3 mutations (38%) that may combine with JAK mutations (15%), while some ALK+ ALCLs (13%) presented STAT3 mutation alone [ 51 ]. The highest pY-STAT3 phosphorylation level is present in ALK- ALCL displaying a typical CD3-CD5- CD7- CD30+ phenotype [ 51 ].…”
Section: Alcl Oncogenesismentioning
confidence: 99%